The Roles of Local Administrative Organizations in Flood Management: The Analysis of the Flood Management Plan of Rangsit City Municipality, Pathumthani Province - มาลา, ไททัศน์; เรืองสม, วิไลลักษณ์; ชิณศรี, วลัยพร (Journal of Politics and Governance, 2018)
This article aimed to inquire the Flood Management Plan of Rangsit City Municipality, which is, plan before, in between, and after the flood using the qualitative research methodology. The research found that Rangsit City Municipality emphasized the Flood Management Plan systematically as follws: (1) Before the flood, there had been surveys of areas which frequently flooded, preparation of flood prevention system, and warning plan for middle-, crisis-, and severe-level warning. In addition, issues concerning the improvement of flood prevention were filed in the Annual Municipal improvement plan. (2) In between the incident of flood, there had been a war room looking after the problems caused by the storm or landslide, the Rangsit City Municipality emphasized in the preparation for 7 sanctuary areas that can handle 1,980 people, there had been organizing of clear responsibilities within the organization. (3) After the flood, the emphasis is placed on the restructuring of infrastructure for flood prevention, that is sewage pipeline, pumping pool and maximization of drainage efficiency.